(3EHWGd fgL GdHGWd , hEgeGd cTa GdYGWds - (3GdNfLj, GdGUHgGfj, NhGLg ehdGfG, GdaVd Hf QhR HgGf Hf aVd Gddg, b (B9s ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg (B...(3aEf cJGHg eTJed Ydi eWGYf GdNdaGA GdQGTOjf hGdCeI GdeQVjjf hPcQ eKGdH GdYdeGA GdeLJgOjf agh aj gPG ceG PQ HYV GdXQaGA Ydi eG jVYhfg Ydi CdSfI GHgGFe Cf GdLeGd SCd LedG ef Cjf JNQL bGd GdLeGd ef GdMeGe bGd UObJ XGgQG (B...s
(3BNQgG (B:s
... (3Cfg bGd EPG XgQJ GdHOYI aj CeJj adjfXQ GdYGde Ydeg hEf de jaYd aYdjg dYfI Gddg hCfG GYhP HGddg ef dYfJg hYbGHg hQOg hYPGHg hdgPG GTJZdJ HJOhjf gPG GdcJGHs
(3JHUQI GdYfhGf (B:s
(3GdQO Ydi fgL GdUOb hcTa GdMb dGHf GdeWgQ GdMdj , hPcQg UGMH GdPQjYI aj eYQV PcQg dcJGH EMbGb GdMb ddbGVj fhQ Gddg GdTgjOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajfs
(3GdPQjYI (B1\1521s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds